The Use of “LIBAT” Methods (See – Read – Write) to Improve Student Learning Outcomes in Arabic Lenguage Subjects Kitabah Materials - Ade Arip Ardiansyah; Alna Ningsih; Iis Barokah (Gunung Djati Conference Series, 2023)
This research stems from the problems of teaching Arabic that students feel in the ninth grade at "Ibnu Jabal" Islamic Secondary School, Cicalengka Bandung, which is their difficulty in writing. Therefore, the teacher needs to choose the appropriate teaching method to improve the students' academic achievement. The purposes of this research are to know the students' achievement in the Arabic language for writing before and after using the “LIBAT” method. Knowing the level of students' achievement in the Arabic language for writing after using it. As for the method used in this research, it is a semi-experimental method, with one group design, with pre- and post-test. Using a data collection method such as observation, interview, test and documentation. The use of this method in teaching the Arabic language to the subject of writing improves the students' academic achievement in the Arabic language for the subject of writing. As indicated by the result obtained from the value of the mean n-d at the rate of 0.51 or 51%, this result indicates a moderate degree in the interpretation criterion